2015
DOI: 10.4103/2277-9531.162372
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the efficacy of psychological and educational interventions to improve academic performance of students with learning disabilities in Iran

Abstract: Introduction:with due attention to the importance of learning disabilities and necessity of presenting interventions for improvement of these disorders in order to prevent future problems, this study used meta-analysis of the research model on the impact of psychological and educational interventions to improve academic performance of students with learning disabilities.Methods:with the use of meta-analysis method by integrating the results of various researches, this study specifies the effect of psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…In other words, the present study aimed to rigorously test the efficacy of training basic numerical abilities based on sufficiently long durations across a large range of magnitudes while minimizing the influence of test–retest effects. The duration of training in the present study was longer than that of other lab-based training studies (but it was similar to the average duration of intervention/training programs commonly used in real-world educational settings ( Cohen et al, 1982 ; Kroesbergen and Van Luit, 2003 ). Furthermore, we carefully controlled for non-numerical visual properties of the non-symbolic stimuli (dot arrays) during training and assessment, so that the influence of non-numerical visual magnitudes can be minimized.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…In other words, the present study aimed to rigorously test the efficacy of training basic numerical abilities based on sufficiently long durations across a large range of magnitudes while minimizing the influence of test–retest effects. The duration of training in the present study was longer than that of other lab-based training studies (but it was similar to the average duration of intervention/training programs commonly used in real-world educational settings ( Cohen et al, 1982 ; Kroesbergen and Van Luit, 2003 ). Furthermore, we carefully controlled for non-numerical visual properties of the non-symbolic stimuli (dot arrays) during training and assessment, so that the influence of non-numerical visual magnitudes can be minimized.…”
Section: Introductionsupporting
confidence: 48%
“…Exact, symbolic arithmetic practice during training was purposefully excluded in order to thoroughly test whether the effect of training on basic numerical cognition truly transfers to exact, symbolic math ability without explicit practice in this domain. Our software was designed to include several training modules within each session, as in typical educational interventions ( Kroesbergen and Van Luit, 2003 ; Gersten et al, 2009 ; Codding et al, 2011 ). Training sessions were administered at the child’s home which increased ecological validity of our training to real-world educational applications.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that direct accuracy feedback (possibly with some cost attached to incorrect solutions) may be conducive to beneficial changes in strategy choices. They also show that considerable changes in strategy choices and improvements in performance may be achieved with as few as three training sessions of 15 min (in line with the finding of Kroesbergen and Van Luit, 2003 , who found that longer mathematics interventions are not necessarily more effective). As said, a follow-up test after a longer period of time (e.g., several months) should be used to establish whether the changes are lasting.…”
Section: Discussionsupporting
confidence: 78%
“…Using a pretest-training-posttest design, an explicit-scaffolding training condition designed to promote writing down calculations was compared to a practice-only training condition where strategy use was not explicitly targeted. The explicit-scaffolding training involved a step-by-step problem-solving plan for multi-digit division problems, based on the principles of direct, explicit instruction that lower-ability students tend to profit from ( Kroesbergen and Van Luit, 2003 ; Gersten et al, 2009 ). The practice-only training involved practicing problem solving only, without explicit scaffolding, but with feedback on the accuracy of the outcome as in the explicit-scaffolding condition.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, extensive research has been conducted on how adults with learning disabilities cope with the challenges of the education system: cognitive assignments, disappointment of family and peers regarding their social competence, and disappointment with oneself, low self-image, and concealment of emotions (Faramarzi, Shamsi, Samadi, & Ahmadzade, 2015;Lorger, Shmidt, & Vukman, 2015;Shehu & Zhilla, 2015).…”
Section: Introductionmentioning
confidence: 99%